CEO overconfidence and bondholder wealth effects: Evidence from mergers and acquisitions - Chen, Sheng-Syan; Ho, Keng-Yu; Ho, Po-Hsin; Nie, Wei-Ying (Journal of Corporate Finance, 2022)
This study explores the influence of chief executive officer (CEO) overconfidence on acquirer bondholder wealth in mergers from 1994 to 2019. We find that CEO overconfidence benefits acquirer bondholders. Overconfident CEOs are likely to choose targets with lower return correlations rather than targets with lower risk than acquirers. We further show there is a positive wealth effect during announcement periods as well as firm risk reduction and a positive long-run bond market reaction subsequent to merger completion when overconfident acquirers merge with targets that are less correlated. Overall, the coinsurance effect dominates the liquidity effect on overconfident acquirer bondholder wealth during a merger.